Pendaftaran Objek Fidusia Sebagai Jaminan Utang - Nandang Kusnadi; Ukar Sukarna; Wahyu Budi Susanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Currently, many financial institutions (finance) and banks (commercial banks and credit) provide financing for consumers (consumer finance), leasing (leasing), and factoring (factoring). They generally use agreement procedures that include the existence of fiduciary guarantees for fiduciary objects, but in reality, there are still agreements made under the hands in other words, the fiduciary guarantee object is not registered at the Fiduciary Registration Office. Therefore, this article is to find out the registration of fiduciary objects as debt guarantees and legal protection for debtors. This article is analyzed using a normative juridical approach which is researched from library materials and interprets theoretical matters concerning the conception, principles, legal norms, and doctrines related to the fiduciary object as a debt guarantor which is the subject of the problem. As a result, the party (the debtor) does not neglect his rights and responsibilities as a debtor. Because when the debtor intentionally or due to circumstances is proven to be negligent or breach of contract, the legal protection for the debtor is weak or has no legal force.